Analysis of Risk Factors for Heart Failure in Outpatients at The Undata Regional General Hospital, Central Sulawesi Province - Afni, Nur; Amalinda, Finta; Asriyani, Nadia (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2025)
Heart failure is one of the highest causes of death from cardiovascular disease, especially in middle and low income countries. This study aims to analyze the risk factors for heart failure in outpatients at Undata Hospital, Central Sulawesi Province. This study uses an approach case-control with a total sample of 134 respondents, consisting of 67 cases and 67 controls determined through techniques purposive sampling. Primary data was collected through structured questionnaires, while secondary data was obtained from hospital medical records. Data analysis was carried out using univariate and bivariate approaches using tests Odds Ratio (OR) to determine the relationship between independent variables (obesity, physical activity, smoking history) and the incidence of heart failure. The results showed that obesity had an OR of 1.149 (95% CI: 0.553–2.385), physical activity had an OR of 3.436 (95% CI: 1.048–11.273), and smoking history had an OR of 1.446 (95% CI: 0.655–3.194). These findings indicate that physical inactivity is a significant risk factor for heart failure, while obesity and smoking also contribute although not statistically significant. This research emphasizes the importance of preventive intervention on lifestyle factors to reduce the incidence of heart failure in society.